Impact of meibomian gland width on successful contact lens use. Issue 6 (December 2019) - Pucker, Andrew D.; Jones-Jordan, Lisa A.; Kunnen, Carolina M.E.; Marx, Sebastian; Powell, Daniel R.; Kwan, Justin T.; Srinivasan, Sruthi; Sickenberger, Wolfgang; Jones, Lyndon
Abstract: Purpose: To evaluate meibomian gland (MG) width and determine its impact on successful contact lens (CL) use and ocular health. Methods: A five-site study was conducted by recruiting 18- to 45-year-old subjects who had dropped out of CLs because of discomfort. CL dropouts were compared to age- and sex-matched successful CL wearers. Right eyes were evaluated for tear break-up time, tear meniscus height, MG expressibility, meibum quality, and meibography. Central MG widths were evaluated with a custom MATLAB program. Results: CL dropouts (n = 56) and successful CL (n = 56) wearers had similar grades for upper (p = 1.0) and lower (p = 0.22) MG atrophy, upper (p = 0.07) and lower (p = 0.89) MG tortuosity, and upper (p = 0.92) and lower (p = 0.97) MG widths. Upper eyelid MG widths were narrower than lower eyelid MG widths (p = 0.03). Upper and lower MG tortuosity (p < 0.001) and widths (p = 0.03) were associated, but not atrophy (p = 0.42). Lower eyelid MG widths were associated with MG expressibility (p = 0.01), but MG widths were not with any other factors. Conclusions: Successful CL wear does not appear to be clinically influenced by MG width or other measures of MG structural integrity. Lower eyelid MGs were wider than upper eyelid MGs and narrower lower eyelid MGs were associated with worse MG expressibility, suggesting that narrower MGs may produce abnormal meibum. Data also suggests that MG factors of both eyelids should be evaluated in practice.